Accurate Diagnosis and Treatment of Painful Temporomandibular Disorders: A Literature Review Supplemented by Own Clinical Experience - Adam Andrzej Garstka; Lidia Kozowska; Konrad Kijak; Monika Brzózka; Helena Gronwald; Piotr Skomro; Danuta Lietz-Kijak (Pain Research and Management)
Introduction. Temporomandibular disorders (TMD) is a multifactorial group of musculoskeletal disorders often with combined etiologies that demand different treatment plans. While pain is the most common reason why patients decide to seek help, TMD is not always painful. Pain is often described by patients as a headache, prompting patients to seek the help of neurologists, surgeons, and ultimately dentists. Due to the unique characteristics of this anatomical area, appropriate diagnostic tools are needed, as well as therapeutic regimens to alleviate and/or eliminate the pain experienced by patients. Aim of the Study. The aim of this study is to collect and organize information on the diagnosis and treatment of pain in TMD, through a review of the literature supplemented by our own clinical experience. Material and Methods. The study was conducted by searching scientific databases PubMed, Scopus, and Google Scholar for documents published from 2002–2022. The following keywords were used to build the full list of references: TMD, pain, temporomandibular joint (TMJ), TMJ disorders, occlusal splint, relaxing splints, physiotherapy TMD, pharmacology TMD, natural therapy TMD, diagnostic criteria for TMD, and DC/TMD. The literature review included 168 selected manuscripts, the content of which was important for pain diagnosis and clinical treatment of TMD. Results. An accurate diagnosis of TMD is the foundation of appropriate treatment. The most commonly described treatments include physiotherapy, occlusal splints therapy, and pharmacological treatment tailored to the type of TMD. Conclusions. Based on the literature review and their own experience, the authors concluded that there is no single ideal form of pain therapy for TMD. Treatment of TMD should be based on a thorough diagnostic process, including the DC/TMD examination protocol, psychological evaluation, and cone beam computer tomography (CBCT) imaging. Following the diagnostic process, once a diagnosis is established, a treatment plan can be constructed to address the patient’s complaints.